MANAJEMEN KEUANGAN MASJID AL-HILAL SURABAYA DALAM PERSPEKTIF MASLAHAH MURSALAH - Imron, Sulkan; Ibdalsyah, Ibdalsyah; Ayuniyyah, Qurroh (Al-Infaq: Jurnal Ekonomi Islam, 2022)
Maslahah mursalah is the argument for establishing a new problem that has not been explicitly mentioned in the main sources, the Qur'an and hadith, either accepted or rejected. In this study, the author focuses on finance to describe and analyze in depth the management of Al-Hilal Mosque in Surabaya in the production, distribution, and consumption of infaq funds from the perspective of maslahah mursalah. The methodology used in this research is descriptive qualitative with a case study approach and literature. The results of this study indicate that the financial management of Al-Hilal Mosque Surabaya in 2021, both in the production, distribution, and consumption sectors of infaq funds have legal similarities in the perspective of maslahah mursalah. The similarities include: First, based on the content, it is included in the maslahah ammah category. Second, based on its nature, it is included in the category of maslahah mutaghayirah.Third, based on the level of human needs and interests, it is included in the maslahah dharuriyah category. Fourth, based on the existence and category with Shari'a, it is included in maslahah mu'tabarah (which is acceptable) and maslahah mursalah.